2019
DOI: 10.5056/jnm19045
|View full text |Cite
|
Sign up to set email alerts
|

Five-fold Gastrointestinal Electrical Stimulation With Electromyography-based Activity Analysis: Towards Multilocular Theranostic Intestinal Implants

Abstract: Background/Aims Motility disorders are common and may affect the entire gastrointestinal (GI) tract but current treatment is limited. Multilocular sensing of GI electrical activity and variable electrical stimulation (ES) is a promising option. The aim of our study is to investigate the effects of adjustable ES on poststimulatory spike activities in 5 GI segments. Methods Six acute porcine experiments were performed with direct ES by 4 ES parameter sets (30 seconds, 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…The highest spike counts were found in the small bowel of both the conventional (jejunum) and robotic (ileum) setup. This result is consistent with our previous findings [15] and other studies. Romański et al [20]and Lammers et al [21]reported a higher number of Spm in the jejunum and ileum of pigs and dogs than in the human stomach and duodenum [22] and the porcine colon [23].…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…The highest spike counts were found in the small bowel of both the conventional (jejunum) and robotic (ileum) setup. This result is consistent with our previous findings [15] and other studies. Romański et al [20]and Lammers et al [21]reported a higher number of Spm in the jejunum and ileum of pigs and dogs than in the human stomach and duodenum [22] and the porcine colon [23].…”
Section: Discussionsupporting
confidence: 95%
“…The pre- and poststimulatory EMG analysis, spike detection, and statistical analysis were based on our previous study [15]. Minute-by-minute EMG spike activity was analyzed using data at 5 locations from 5 experiments ( n = 25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…of colonic neuromodulation on healthy pigs has been the object of a limited number of reports so far. Most of these studies involve acute direct ES on anesthetized and cleansed descending colon [34][35][36][37] or cecum 38,39 using a broad range of stimulation parameters (5-130 Hz, 0.03-3 ms, 7-30 mA). These protocols induce local contractions (single point of stimulation), 35,39 propulsive contractions, [37][38][39] luminal content movement, 36,39 or acceleration of colonic transit in response to sequential stimulations.…”
Section: Key Pointsmentioning
confidence: 99%
“…Most of these studies involve acute direct ES on anesthetized and cleansed descending colon [34][35][36][37] or cecum 38,39 using a broad range of stimulation parameters (5-130 Hz, 0.03-3 ms, 7-30 mA). These protocols induce local contractions (single point of stimulation), 35,39 propulsive contractions, [37][38][39] luminal content movement, 36,39 or acceleration of colonic transit in response to sequential stimulations. 36,37,40 These data confirmed or expanded other preclinical studies performed in healthy [41][42][43][44] or constipation models 45,46 in rodents, cats, and dogs.…”
Section: Key Pointsmentioning
confidence: 99%